Determinación de alcohol metílico mediante el método de cromatografía de gases en muestras de orina de cadáveres que ingresan al laboratorio dequímica forense del departamento de criminalistica de chimborazo durante el periodo de diciembre 2011 a abril 2012 - Parra Casco, Nataly Margarita (2013)
Determination of methyl alcohol by the method of gas chromatography in urine samples of curpses admitted at the Forensic Chemistry Laboratory of the Departament of Criminology of Chimborazo during the period December 2011 to April 2012. The following study was conducted to determine the importance of the analysis of methanol which is the main component of dry distilled wood.